Effect of EMIC waves on relativistic and ultrarelativistic electron populations: Ground‐based and Van Allen Probes observations. Issue 5 (6th March 2014) - Usanova, M. E.; Drozdov, A.; Orlova, K.; Mann, I. R.; Shprits, Y.; Robertson, M. T.; Turner, D. L.; Milling, D. K.; Kale, A.; Baker, D. N.; Thaller, S. A.; Reeves, G. D.; et al.
Abstract We study the effect of electromagnetic ion cyclotron (EMIC) waves on the loss and pitch angle scattering of relativistic and ultrarelativistic electrons during the recovery phase of a moderate geomagnetic storm on 11 October 2012. The EMIC wave activity was observed in situ on the Van Allen Probes and conjugately on the ground across the Canadian Array for Real‐time Investigations of Magnetic Activity throughout an extended 18 h interval. However, neither enhanced precipitation of >0.7 MeV electrons nor reductions in Van Allen Probe 90° pitch angle ultrarelativistic electron flux were observed. Computed radiation belt electron pitch angle diffusion rates demonstrate that rapid pitch angle diffusion is confined to low pitch angles and cannot reach 90°. For the first time, from both observational and modeling perspectives, we show evidence of EMIC waves triggering ultrarelativistic ( 2–8 MeV) electron loss but which is confined to pitch angles below around 45° and not affecting the core distribution.